The prognostic impact of objective nutritional indices in elderly patients with ST-elevation myocardial infarction undergoing primary coronary intervention. (15th October 2016) - Basta, Giuseppina; Chatzianagnostou, Kyriazoula; Paradossi, Umberto; Botto, Nicoletta; Del Turco, Serena; Taddei, Alessandro; Berti, Sergio; Mazzone, Annamaria
Abstract: Background: The prognostic impact of nutritional status in ST-elevation myocardial infarction (STEMI) patients is poorly understood. Methods: We used the controlling nutritional status (CONUT) score and the prognostic nutritional index (PNI) score on outcomes of 945 patients with acute STEMI undergoing primary percutaneous coronary intervention with stent. Results: During a median follow-up of 2 years (1–3.3 years, interquartile range), 56 patients (5.9%) died for all-cause of death. In the dead group, the CONUT and PNI scores were more severe than in the alive group. Elderly patients (≥ 71 years) had nutritional indices more serious than patients < 71 years. In the whole population of the study, both CONUT and PNI correlated with clinical markers of poor prognosis such as brain natriuretic peptide (BNP), creatinine and liver enzymes. Kaplan–Meier curves revealed that the patients with severe CONUT but not patients with severe PNI index had the highest event rate for all-cause death, with a log-rank of p < 0.001. The Cox proportional hazard analyses showed that, contrary to PNI score, the CONUT score was associated with increased risk of all-cause death for both unadjusted model and age- and sex-adjusted model, while in a full-adjusted model the best predictors were age and BNP. Conclusions: In STEMI patients, the nutritional status evaluated by the CONUT score, in addition to other comorbidities, can affect the prognosis in elderly patients. These results suggest a personalized nutritional treatment as well as an accurate assessment of the appropriateness of lipid-lowering treatment after coronary revascularization.